2014
DOI: 10.1175/jtech-d-11-00202.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EarthCARE Cloud Profiling Radar Doppler Velocity Measurements in Particle Sedimentation Regimes

Abstract: The joint European Space Agency-Japan Aerospace Exploration Agency (ESA-JAXA) Earth Clouds, Aerosols and Radiation Explorer (EarthCARE) mission is scheduled for launch in 2016 and features the first atmospheric Cloud Profiling Radar (CPR) with Doppler capability in space. Here, the uncertainty of the CPR Doppler velocity measurements in cirrus clouds and large-scale precipitation areas is discussed. These regimes are characterized by weak vertical motion and relatively horizontally homogeneous conditions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 29 publications
2
84
0
Order By: Relevance
“…2b, we examine the modeled and measured CloudSat reflectivity difference between horizontally separated points, similar to the study by Kollias et al (2014). Overall, the correspondence is rather good, indicating that the horizontal variability of reflectivity is captured well by the combination of NICAM and the scattering model.…”
Section: Validationmentioning
confidence: 66%
“…2b, we examine the modeled and measured CloudSat reflectivity difference between horizontally separated points, similar to the study by Kollias et al (2014). Overall, the correspondence is rather good, indicating that the horizontal variability of reflectivity is captured well by the combination of NICAM and the scattering model.…”
Section: Validationmentioning
confidence: 66%
“…In Kollias et al . [], the focus was on high‐level ice clouds, and thus, simulation of the surface return was not included. However, the surface echo is an important feature that restricts the detection of low‐level clouds by spaceborne radars [ Tanelli et al ., ]; therefore, for this study, the surface echo is introduced in the simulator and is described here.…”
Section: Simulator Data and Processingmentioning
confidence: 99%
“…In low signal‐to‐noise ratio (SNR) conditions, random noise will dominate velocity estimates [ Kollias et al ., ]. In addition, the satellite's motion of 7 km s −1 combined with the EC‐CPR antenna's beam width will both broaden the observed Doppler spectra and, in the case of nonuniform beam filling (NUBF), introduce biases that can reach several meters per second [ Kollias et al ., ; Tanelli et al ., ; Schutgens , ]. Biases of similar magnitudes are produced by mispointing of the CPR antenna away from the nadir direction by even a few microrad [ Battaglia and Kollias , ].…”
Section: Introductionmentioning
confidence: 99%
“…The red and green arrows indicate the apparent velocity introduced to the WIVERN volume as a result of the motion of the satellite (green toward and red away from the satellite); as a result, for the case illustrated, a downward bias will be produced. Notional studies have demonstrated that such biases can be mitigated by estimating the alongtrack reflectivity gradient (Schutgens 2008;Kollias et al 2014;Sy et al 2014). For WIVERN the relevant gradients are those along the direction in the plane generated by the satellite velocity and by the antenna boresight and are orthogonal to the latter (identified by η in Fig.…”
Section: Nonuniform Beam Filling (Nubf)mentioning
confidence: 99%
“…When dealing with spaceborne millimetric radars, in the presence of highly attenuating media, the multiple-scattering signal can overwhelm the single-scattering contribution (Battaglia et al 2010) with very detrimental effects both on retrieval and Doppler products (Battaglia and Kollias 2014). Studies based on CloudSat have demonstrated that multiple scattering is not negligible in the presence of high-density ice (hail and graupel) or moderate/ intense rain (Battaglia et al 2011).…”
Section: Nonuniform Beam Filling (Nubf)mentioning
confidence: 99%